Do behaviour change techniques increase adherence to home exercises in those with upper extremity musculoskeletal disorders? A systematic review. (16th December 2020) - Thacker, Jonathan; Bosello, Francesca; Ridehalgh, Colette
Abstract: Objectives: To investigate whether behaviour change techniques (BCTs) can influence adherence to home exercise in people with upper extremity musculoskeletal disorders (UEMD). Design: A systematic review of randomised control trials, non‐randomised control trials, case–control studies and cohort studies. Results were presented narratively. Participants were those with UEMD. The intervention was any home exercise programme, alongside a BCT designed to increase exercise adherence. Any duration of intervention was accepted. The main outcome sought was adherence to home exercise. A systematic search was performed on four online databases. Grey literature was searched. Results: The search resulted in 28, 755 titles. 77 full‐text articles were assessed for eligibility. Six studies were included in the qualitative synthesis. Four studies had Some Concern of Bias, whilst two studies had High Risk of Bias. Three studies found statistically significant differences in exercise adherence ( p < 0.05) between the Intervention group and Control group. The BCT 'Social Support (unspecified)' was used within all studies that found significant differences in adherence levels at outcome. However, multiple BCTs were received by the Intervention groups within all studies, making it impossible to identify the effects of any single BCT upon adherence levels. Conclusion: Social support may be relevant in patients' adherence levels to HEPs. However, confidence in the results is uncertain given the small number of studies found, and their High RoB. Future studies should validate their measurement and definition of adherence, as well as the number of BCTs they use, to provide reproducible evidence.